A Balanced View of Efficacy and Safety of Aspirin in Cardiovascular Diseases - Casado-Arroyo, Rubén; Lanas, Angel; Brugada, Pedro (Current Pharmaceutical Design, 2015)
This review highlights practical aspects related to aspirin therapy in cardiovascular diseases, specifically, the benefits and hazards in different clinical settings. Aspirin reduces one fourth of all major cardiovascular events but also increases major gastrointestinal bleeds by about half. As with other cardiovascular prevention strategies, the absolute benefit of aspirin is linearly related to the cardiovascular risk of the patient. The risk-benefit of aspirin can vary substantially in different settings: in secondary prevention, the benefits usually outweigh the excess of major bleeding complications. In primary prevention, it is not unusual that the number of vascular events avoided equals the number of major bleeds induced by aspirin. Finally, there is a growing body of evidence suggesting that aspirin may interfere with the early stages of cancer, metastasis and mortality. For all these reasons, in this article new developments in the field directed towards individualized risk assessment strategies are also discussed.
Keywords: Aspirin